Civilizational Aspects of the Griminals Peoples of Southern Libya The ancients from the ninth century B.C. to the seventh century A.D. - Historical study- (Damascus University Journal of Historical Studies, 2022)
The Griminals tribe is one of the most important ancient Libyan tribes because it enjoyed a good reputation and close relations with its neighboring peoples. In addition to its great fame, as it was the one who had the greatest credit for the development and prosperity of the south of Libya, especially on the economic level, for its great role in linking the southern Libyan regions with the coastal cities of commercial fame, through its control of the trade routes linking the Libyan coast and the center of the African continent, and its role in playing the role of commercial mediation between them.It was also able to build a prosperous civilization in this dry desert region in its various aspects such as politics, so it established a centralized monarchy based on military power in which all powers and authorities were concentrated in the hands of the king elected by the tribal council of elders, and it also overcame all the obstacles it contained from drought, high temperature and soil Saline, by innovating distinctive means and tools that constituted a qualitative leap in its time, especially in the field of agriculture, with what was known as the “Al-Fajarat” system for industrial irrigation.This enriched it with many diverse crops that constituted the main resource for the food needs of its inhabitants.It also worked on raising many animals that it relied on to carry out its activities and to secure the food and clothing of its people.
Keywords: Civilizational Aspects of the Griminals Peoples of Southern Libya The ancients from the ninth century B.C. to the seventh century A.D. - Historical study-